Don't blink - Patterson, James, 1947-; Roughan, Howard (New York, NY : Little, Brown and Co., 2010)
The good: New York's Lombardo's Steak House is famous for three reasons, the menu, the clientele, and now, the gruesome murder of an infamous mob lawyer. Effortlessly, the assassin slips through the police's fingers, and his absence sparks a blaze of accusations about who ordered the hit. The bad: Seated at a nearby table, reporter Nick Daniels is conducting a once-in-a-lifetime interview with a legendary baseball bad boy. In the chaos, he accidentally captures a key piece of evidence that lands him in the middle of an all-out war between Italian and Russian mafia forces. NYPD captains, district attorneys, mayoral candidates, media kingpins, and one shockingly beautiful magazine editor are all pushing their own agendas on both sides of the law. And the dead: Back off or die is the clear message Nick receives as he investigates for a story of his own. Heedless, and perhaps in love with his beautiful editor, Nick endures humiliation, threats, violence, and worse in a thriller that overturns every expectation and finishes with the kind of flourish only James Patterson knows
Keywords: Lawyers -- Crimes against -- Fiction; Journalists -- Fiction; Assassination -- Investigation -- Fiction; Gangsters -- Fiction; New York (N.Y.) -- Fiction; Thrillers (Fiction).; Large print books; Detective and mystery fiction